2015
DOI: 10.1108/el-12-2012-0159
|View full text |Cite
|
Sign up to set email alerts
|

Influence of motivational factors on utilisation of Internet health information resources by resident doctors in Nigeria

Abstract: Background The internet is a huge library with avalanche of information resources including healthcare information. There are numerous studies on use of electronic resources by healthcare providers including medical practitioners however, there is a dearth of information on the patterns of use of web-based health information resource by resident doctors in Nigeria. This study therefore investigates the influence of internet accessibility and demographic factors on utilization of web-based health information re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…Zhang (2011) found that social networking sites' (SNS) perceived usefulness and perceived ease of use have an impact on college students' user intention of SNS to access health information. Kim (2015) and Ajuwon and Popoola (2015) came to the same conclusion in research on other health information systems. And many researchers have applied the TAM to the field of health information seeking.…”
Section: Research Hypothesissupporting
confidence: 48%
See 1 more Smart Citation
“…Zhang (2011) found that social networking sites' (SNS) perceived usefulness and perceived ease of use have an impact on college students' user intention of SNS to access health information. Kim (2015) and Ajuwon and Popoola (2015) came to the same conclusion in research on other health information systems. And many researchers have applied the TAM to the field of health information seeking.…”
Section: Research Hypothesissupporting
confidence: 48%
“…A summary of the literature (Khazer & Ganaie, 2014) in recent years indicates that research into information-seeking behavior mainly concentrates on two aspects of online searches: job-related information and daily information (Figure 1). And health information-seeking behavior has become an increasingly important issue in daily information-seeking behavior studies (Ajuwon & Popoola, 2015;Kim, 2015). When it comes to the process of information search, the related studies tend to focus on user information needs, the selection of information channels, and certain influencing factors of information-seeking behaviors (Zhang, Liu & Yang, 2008).…”
Section: Effects Of Situation On Information-seeking Behaviormentioning
confidence: 99%
“…This is a reflection of the fact that there were relatively more resident doctors than consultants, and the demographic characteristics mirror similar published studies with large number of residents. [7] The highest agreement was for fundamental assumption 2 "adults have accumulated a great deal of experience, which is a rich resource for learning" which had an overall 89.3% of the respondents in agreement. The least agreement (49.1%) was for fundamental assumption 4.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified various demographic characteristics which determine internet use. Among these are Ajuwon and Popoola (2014) who stated that age is a characteristic that have been found to play a substantial role in influencing internet usage. According to the authors, youths tend to be more comfortable with using computer and the internet than adults.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2015) indicate that male undergraduate students reported higher internet addiction than their female counterparts. Similarly, Ajuwon and Popoola (2014) assert that males are more internet savvy than females. Servidio (2014) demonstrated in his findings that males were more inclined to use the Internet than females.…”
Section: Literature Reviewmentioning
confidence: 99%